The path of Handsome Lake : a model of recovery for native people - Walle, Alf H. (Emerald Publishing Limited : IAP-Information Age Pub., 2004)
This group of essays is written to provide a series of suggestions to Native people who seek to deal with alcoholism from the perspective of their unique heritages and with an understanding that the pressures to which Native traditions and societies have been subjected may trigger dysfunctional behavior, such as excessive drinking.
Keywords: Handsome Lake, -- 1735-1815.; Indians of North America -- Alcohol use.; Indians of North America -- Counseling of.; Indians of North America -- Rehabilitation.; Social work with Indians -- United States.; Alcoholism -- Treatment -- United States.; Alcoholics -- Rehabilitation -- United States.; Self-help -- Substance Abuse & Addictions -- Alcohol.; Coping with, advice about drug and alcohol problems.; elektronické knihy; electronic books